Comminuted Patella Fracture in Elderly Patients: A Systematic Review and Case Report - Brent Matthews MBBS; Kaushik Hazratwala MBBS (FRACS); Sergio Barroso-Rosa MD (Geriatric Orthopaedic Surgery & Rehabilitation, 2017)
Objectives: To review comminuted patella fracture in the elderly patients and examine the surgical options to avoid complications such as fixation failure and poor functional outcome. To provide an example of mesh augmentation in comminuted patella fracture in the elderly patients. Data Sources: A literature review was conducted by the authors independently using Ovid, Medline, Cochrane, PubMed, and Clinical Key in English. We aimed to review data on patients older than 65 with comminuted patella fracture. Search conducted between July and December 2015. Study Selection: Search terms included patella fracture, elderly, and fixation failure. Abstracts were included if they were a case report, cohort series, or randomized control trial. Further inclusion criteria were that they were available in full text and included patient age(s), operative details, follow-up, and outcome discussion. Data Extraction: Each study was assessed according to its level of evidence, number of patients, age of patients, fracture patterns described, complications of treatment, and results summarized. Data Synthesis: Paucity of data and heterogeneity of studies limited statistical analysis. Data are presented as a review table with the key points summarized. Conclusion: In patella fracture, age >65 years and comminuted fracture pattern are predictors of increased fixation failure and postoperative stiffness, warranting special consideration. There is a trend toward improved functional outcomes when augmented fixation using mesh or plates is used in this group. Further level 1 studies are required to compare and validate new treatment options and compared them to standard surgical technique of tension band wire construct.